Falling behind or catching up? Developing countries in the era of globalization - Erich Gundlach; Peter Nunnenkamp (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
Globalization improves the prospects for developing countries (DCs) to catch up economically with industrialized countries. But not all DCs will automatically benefit from globalization. Some DCs even face the risk of being delinked from the international division of labor. Differences in DC economic policies ultimately determine whether there will be a deepening divide between rich and poor countries in the world economy. Many observers draw an overly pessimistic picture of the perspectives of DCs in the era of globalization because of missing institutionalized links to regional integration schemes in Europe and North America, a low level of interfirm technology cooperation between industrialized countries and DCs, and a high concentration of foreign direct investment (FDD flows on only a few DC hosts. However, such concerns are largely unfounded: Asian DCs are most successful in globalization although they have remained outside institutionalized integration schemes, while ACP countries have not made much progress despite their preferential access to EU markets. Technology transfers between industrialized countries and DCs mainly occur through FDI and trade in capital goods, rather than through interfirm technology cooperation. Recent trends in FDI and international trade strongly support the proposition that DCs have become closely integrated into globalization strategies. A high concentration of FDI flows on a few DC hosts does not imply that new attractive locations cannot compete for international capital. Admittedly, it is true that between two thirds and three quarters of total FDI flows to DCs have persistently been absorbed by ten host economies. But the country composition of this group has changed over time. Globalization implies an increase in international investment cooperation. Case studies for selected DC industries show that FDI prevails in industries applying sophisticated technologies, whereas licensing and subcontracting are favored when production processes are standardized. Policy interventions may limit the choices open to investing foreign firms and, thereby, cause substitution effects between different forms of globalization or hinder globalization at all. The quality of DC economic policies determines whether these countries will succeed in joining the globalization club. The experience of the frontrunners among DCs suggests some basic policy conclusions: Openness towards world markets is a precondition for becoming involved in globalization strategies of transnational corporations. Liberalizing all forms of international investment cooperation and removing barriers to international trade should rank high on the policy agenda of DCs. Under conditions of globalized production, DC governments are increasingly constrained in pursuing policies of their own liking. Those DCs characterized by pronounced macroeconomic instability are relatively unattractive locations for international investors. Investment in physical and human capital plays a crucial role in enabling DCs to participate in globalization. Economic policies that discourage domestic saving and investment must be avoided. Financial market reforms are needed in DCs characterized by financial repression and inefficient intermediation between savers and investors. A better education of the workforce is required for a successful application of new technologies that become available through globalization.
Keywords: 330; Globalisierung; Internationale Unternehmenskooperation; Direktinvestition; Exportinduziertes Wachstum; Entwicklungskonvergenz; Entwicklungsländer; Welt